2011
DOI: 10.3382/ps.2011-01432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast muscle meat quality in 2 broiler breeds

Abstract: On the basis of meat quality traits, muscle fiber characteristics, and nutrient components and contents in chickens at market age, 120-d-old Beijing-you (BJY) chickens (the Chinese local breed) had distinct breast muscle features when compared with 42-d-old Arbor Acres (AA) chickens (the genetically improved broiler line). The phospholipid (P < 0.05) and essential fatty acid (P < 0.05) contents in BJY chickens were significantly higher than those in AA chickens. No differences (P > 0.05) were found between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 25 publications
2
56
1
Order By: Relevance
“…The BJY chicken is one representative indigenous breed in China [16], a color-feathered, slow-growing chicken and has superior quality of meat products [17], [18]. Most of the traits tested showed considerable ranges between maximal and minimal values (Table 3), as would be expected in a population being maintained for the conservation of genetic diversity; this variability would be expected to increase the power of the GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…The BJY chicken is one representative indigenous breed in China [16], a color-feathered, slow-growing chicken and has superior quality of meat products [17], [18]. Most of the traits tested showed considerable ranges between maximal and minimal values (Table 3), as would be expected in a population being maintained for the conservation of genetic diversity; this variability would be expected to increase the power of the GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that muscle characteristics (myofiber diameter, cross sectional area, and density) could proudly influence meat quality. Several studies have shown that smaller fiber size (diameter and area), leads to tender meat [19][20][21][22]. However, a higher myofiber density might partially support a good sensorial perception of taste [23].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the different traditional food cultures across China, native broiler chickens have meat quality characteristics that are often favoured by consumers over those of commercial breeds. Several previous studies found that such characteristics include greater tenderness and preferred flavours [1-3]. Therefore, the native chicken breeds not only contribute to the conservation of poultry genetic resources, but are also of high economic value.…”
Section: Introductionmentioning
confidence: 99%